Monitoring of kidney function in HIV‐positive patients. Issue 8 (6th May 2015) - Yombi, JC; Jones, R; Pozniak, A; Hougardy, J‐M; Post, FA
<x xml:space="preserve">Abstract</x> HIV‐positive patients are at increased risk of developing chronic kidney disease. Although guidelines recommend regular monitoring of renal function in individuals living with HIV, the optimal frequency remains to be defined. In this review, we discuss the renal syndromes that may be identified at an earlier stage via routine assessment of kidney function, and provide guidance in terms of the frequency of monitoring, the most useful tests to perform, and their clinical significance. Specifically, we address whether annual monitoring of kidney function is appropriate for the majority of HIV‐positive patients.